Opera, Sound Recording, and Critical Race Theory - Matthew Timmermans (Current Musicology, 2021)
This review essay considers the relationships among opera, sound recording, and critical race theory, and explores them at a moment when these fields are beginning to converge. One of my concerns will be the recent and ground-breaking studies and collections on opera and race by Naomi Adele André (2017, 2019), Kira Thurman (2012, 2019), Pamela Karantonis and Dylan Robinson (2011), and Mary I. Ingraham, Joseph K. So and Roy Moodley (2016). Another will be the neglected history of opera and sound recording; notable scholars here include Karen Henson (2020), Robert Cannon (2014), and Richard Leppert (2015). Finally, I will focus on the thought-provoking analyses of race and sound by Alexander Weheliye (2005), Brian Ward (2003), Jennifer Lynn Stoever (2016) and Nina Sun Eidsheim (2019). There are obvious connections among these three bodies of scholarship, yet these connections have not yet been clearly identified and explored.